2011
DOI: 10.4061/2011/653903
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hypertension among Patients with Coronary Heart Disease

Abstract: Evidence suggests that coronary heart disease (CHD) is the most common outcome of hypertension. Hypertension accelerates the development of atherosclerosis, and sustained elevation of blood pressure (BP) can destabilize vascular lesions and precipitate acute coronary events. Hypertension can cause myocardial ischemia in the absence of CHD. These cardiovascular risks attributed to hypertension can be reduced by optimal BP control. Although several antihypertensive agents exist, the choice of agent and the appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…34, 35 This endothelial resilience following PGC-1α upregulation is not observed following acute hypertension in vessels relying on a single mediator, including both CAD vessels (H 2 O 2 ) and non-CAD vessels (NO). 9 This observation underscores that PGC-1α upregulation not only restores NO bioavailability and reduces mt H 2 O 2 (i.e., reversal of the CAD phenotype) but also confers additional protection against barotrauma within the context of CAD.…”
Section: Discussionmentioning
confidence: 97%
“…34, 35 This endothelial resilience following PGC-1α upregulation is not observed following acute hypertension in vessels relying on a single mediator, including both CAD vessels (H 2 O 2 ) and non-CAD vessels (NO). 9 This observation underscores that PGC-1α upregulation not only restores NO bioavailability and reduces mt H 2 O 2 (i.e., reversal of the CAD phenotype) but also confers additional protection against barotrauma within the context of CAD.…”
Section: Discussionmentioning
confidence: 97%
“…Hypertension is one of common cardiovascular diseases and also a major risk factor of atherosclerosis, and plays crucial roles in the occurrence and development of coronary heart diseases (CHD) [1]. It has been shown that the amplitude of the increase in blood pressure is linearly correlated with the incidence of CHD [2].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial injury impairs synthesis of the potent vasodilator nitric oxide. This in turn leads to further inflammation and thrombosis by the way of reactive oxygen species and multiple inflammatory markers [3]. Therefore, endothelial injury caused by hypertension (HTN) leads to a cascade of events forming the foundation of CHD development [3].…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II has been shown to increase arterial wall stiffness, thus impairing vascular compliance. In addition, angiotensin II contributes to the development of insulin resistance and stimulates production of proinflammatory molecules that cause vascular inflammation and coagulopathy [2, 3]. The treatment and management of these patients focus on targeting and ameliorating of these pathologic mechanisms in each of these three main high cardiovascular risk populations: (1) patients with CHD, (2) patients with HF, and (3) diabetic patients.…”
Section: Introductionmentioning
confidence: 99%